2008
DOI: 10.1088/1475-7516/2008/06/029
|View full text |Cite
|
Sign up to set email alerts
|

Primordial non-Gaussianities of general multiple-field inflation

Abstract: We perform a general study of the primordial scalar non-Gaussianities in multi-field inflationary models in Einstein gravity. We consider models governed by a Lagrangian which is a general function of the scalar fields and their first-order spacetime derivatives. We use δN formalism to relate scalar fields and the curvature perturbations. We calculate the explicit cubic-order perturbative action and the three-point function of curvature perturbation evaluated at the horizon-crossing. Under reasonable assumptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 107 publications
(237 reference statements)
2
46
0
Order By: Relevance
“…In this mixed scenario, it is also possible to detect the non-Gaussianity generated during inflation in the generalized inflation models [44,45,46,47,48,49,50,51,52]. For another interesting observation in this mixed scenario, the second order non-Gaussianity parameters τ N L and g N L are enhanced for fixed f N L .…”
Section: Discussionmentioning
confidence: 96%
“…In this mixed scenario, it is also possible to detect the non-Gaussianity generated during inflation in the generalized inflation models [44,45,46,47,48,49,50,51,52]. For another interesting observation in this mixed scenario, the second order non-Gaussianity parameters τ N L and g N L are enhanced for fixed f N L .…”
Section: Discussionmentioning
confidence: 96%
“…A similar calculation of the third-order action can be found in [40], but only for the multifield Lagrangians of the form PðX; K Þ, where X ¼ IJ X IJ . The third-order action coming from the gravitational part is the same as in the single-field case and is given by the expression…”
Section: A Third-order Action: General Casementioning
confidence: 94%
“…For general multi-field non-canonical models in slow-roll (which is the situation relevant to our models), utilising the In-In formalism to calculate the statistics of the scalar field perturbations on flat hypersurfaces at horizon crossing it was found that 13) and that [39] A IJK = 1 4…”
Section: )mentioning
confidence: 99%
“…Expressions for c 2 s , u and λ are given in Ref. [39] for non-Canonical models 4 . In this work, we express all of these parameters in terms of three-form quantities using Eqs.…”
Section: )mentioning
confidence: 99%